SKILLS BASED COMPETENCY AND COMPETITIVENESS OF ACCOUNTING PRACTITIONERS IN ASEAN EMERGING MARKET - Sanusi Gazali Pane; Saparuddin Siregar (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Competency frameworks are urgently needed by accounting practitioners within organizations to carry out their roles effectively. Moreover, in the context of economic integration and labor mobility between regional countries, the role of accounting practitioners becomes one of the eight professions affected by professional competition. The purpose of this research is to measure the level of competence of accounting practitioners using competency assessment methods that refer to technical and non-technical assessments through the collection of relevant evidence on accounting work. The results of this study showed that during the testing period of 2018-2020 as many as 83.01 failed to meet the level of competence. While 16.01 percent have competency standards in the qualification of accounting technicians and professional clusters. The implications of these findings illustrate that the difficulty of labor market accessibility in the domestic and regional arena will increase and the resulting competitiveness will be lower.  Improvisation is controlled and relevant to, especially in the world of education by directing a paradigm-based curriculum competency framework. This concept is at least in line with the government's commitment to create superior human resources for Indonesia to grow and be more advanced.